A Comparative Systematic Review of the Optimal CD4 Cell Count Threshold for HIV Treatment Initiation. (20th March 2014) - Olubajo, Babatunde; Mitchell-Fearon, Kathryn; Ogunmoroti, Oluseye
Abstract : HIV infection is no longer characterized by high morbidity, rapid progression to AIDS, and death as when the infection was first identified. While anti-retroviral drugs have improved the outcome of AIDS patients, clinical research on the appropriate time to initiate therapy continues to evolve. Optimal therapy initiation would maximize the benefits of these drugs, while minimizing side effects and drug resistance. Recent 2013 WHO guidelines changed HIV therapy initiation from 350 cells/ μ L to 500 cells/ μ L. This systematic review provides an evidence-based comparison of starting treatment at >500 cells/ μ L with starting treatment at the range between 350 cells/ μ L and 500 cells/ μ L. An 11% increase in risk was detected from initiation therapy at the 350–500 cells/ μ L range (0.37 [0.26, 0.53]), when compared with starting treatment before 500 cells/ μ L (0.33 [0.22, 0.48]). Most individual study comparisons showed a benefit for starting treatment at 500 cells/ μ L in comparison with starting at the 350–500 cells/ μ L range with risks ranging from 19% to 300%, though a number of comparisons were not statistically significant. Overall, the study provides evidence based support for initiating anti retroviral therapy at cell counts >500 cells/ μ L wherever possible to prevent AIDS mortality and morbidity.